Hydro, Wind, and Geothermal: Navigating the Compatibility of Renewable Energy Infrastructure with Tourism - Edita Tverijonaite; Anna Dóra Sæþórsdóttir (Tourism and Hospitality, 2024)
Knowledge of the compatibility of various types of renewable energy infrastructure (REI) with tourism can help avoid conflicts between the energy and tourism sectors and facilitate the energy transition. This study aims to investigate the attitudes of tourism service providers operating in Iceland towards three types of REI—wind, hydro, and geothermal power plants—and identify the factors that shape their perceptions regarding the compatibility between REI and tourism. Mixed research methods were employed to achieve that, which included an online questionnaire survey and semi-structured interviews. The study revealed that tourism service providers were the most positive towards geothermal power plants, followed by hydropower plants, and the most negative towards wind farms. The identified factors that shape their perceptions regarding REI’s compatibility with tourism included landscape and environmental impacts of REI, impacts on tourist attractions, potential of REI as a tourist attraction, perceived reversibility, and the image of REI. These factors help to identify locations where each type of REI is likely to be the most compatible with tourism. Thus, considering them in spatial energy planning is likely to reduce foreseeable conflicts between REI and tourism.